Improving The Teaching Methods of Applied Decorative Arts on The Basis of Creative Educational Technologies - Avezov Sherali Nayimovich (Genius Journals, 2021)
The article provides general information about applied decorative arts. In addition, the methods of teaching applied arts and their application are described in detail. Creative learning technologies that can be used in the teaching of applied decorative arts are also analyzed using examples.
Keywords: Decorative Arts; Methods Of Teaching; Creative Learning Technologies; Creative Plans